Potensi Pemanfaatan Daun Singkong (Manihot utillisima) Terfermentasi Sebagai Bahan Pakan Ikan Nila (Oreochromis sp) - Emyliana Listiowati; Taufik Budhi Pramono (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
ABSTRACTThe purpose of this studied to determine the effect of feeding raw flour made from fermented cassava leaves (Manihot utilissima) on the growth and food convertion ratio and its substitution percentage of feed in providing the best growth of Tilapia fish (Oreochromis sp.). An experimental method used a completely randomized design applying 5 treatments in quadruplicates. The treatments were different percentages of fish meal and cassava leaf in feed rations i.e. P1: 100% and 0%, P2: 75% and 25%, P3: 50% and 50%, P4: 25% and 75%, P5: 0% and 100%. The main parameters were absolute growth, specific growth, daily growth, feed efficiency. Water qualit y parameters were temperature, pH, and dissolved oxygen. Fermented cassava leaf flour (Manihot utilissima) in different percentages affected absolute growth rate, specific growth rate. However, feed convertion rate (FCR) of Tilapia fish (Oreochromis sp.) were not affected. Fermented cassava leaf flour at 25% enabled to provide the best growth and food convertion rate (FCR). Water quality parameters were in optimal conditions for Tilapia fish (Oreochromis sp.) fry.Keywords : growth; feed efficiency; Tilapia fish